Iron overload triggering ECM-mediated Hippo/YAP pathway in follicle development: a hypothetical model endowed with therapeutic implications - Xia, Lingjin; Shen, Yupei; Liu, Suying; Du, Jing (Frontiers in Endocrinology, 2023)
Disruption of iron homeostasis plays a negative role in follicle development. The dynamic changes in follicle growth are dependent on Hippo/YAP signaling and mechanical forces. However, little is known about the liaison between iron overload and the Hippo/YAP signalling pathway in term of folliculogenesis. Here, based on the available evidence, we established a hypothesized model linking excessive iron, extracellular matrix (ECM), transforming growth factor-β (TGF-β) and Hippo/Yes-associated protein (YAP) signal regarding follicle development. Hypothetically, the TGF-β signal and iron overload may play a synergistic role in ECM production via YAP. We speculate that the dynamic homeostasis of follicular iron interacts with YAP, increasing the risk of ovarian reserve loss and may enhance the sensitivity of follicles to accumulated iron. Hence, therapeutic interventions targeting iron metabolism disorders, and Hippo/YAP signal may alter the consequences of the impaired developmental process based on our hypothesis, which provides potential targets and inspiration for further drug discovery and development applied to clinical treatment.